PsycEXTRA Dataset 2010
DOI: 10.1037/e583962011-001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Safety Benefits of a Low-Cost Driving Behavior Management System in Commercial Vehicle Operations: Report

Abstract: FOREWORDMotor vehicle crashes are often predictable and preventable. Yet, many drivers choose to behave in ways that put themselves and others at risk for a vehicle crash and/or serious injuries. At-risk driving behaviors include violating speed limits, excessive speed/lateral acceleration on curves, unplanned lane departures, frequent hard braking, close following distances, lateral encroachment (e.g., during attempted lane changes, perhaps due to improper mirror use), failure to yield at intersections, gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
1
6
0
2
Order By: Relevance
“…Studies (Murray et al, 2006; ATRI, 2011) suggested that moving violations were associated with the risk of truck crashes. Some U.S. companies have used onboard safety monitoring technologies to monitor near misses and provide feedback to truck drivers (Hickman and Hanowski, 2010). Similarly, the U.S. Aviation Safety Reporting System (ASRS) has been collecting confidential, voluntary reports of near misses from pilots, flight attendants, and air traffic controllers since 1976.…”
Section: Discussionmentioning
confidence: 99%
“…Studies (Murray et al, 2006; ATRI, 2011) suggested that moving violations were associated with the risk of truck crashes. Some U.S. companies have used onboard safety monitoring technologies to monitor near misses and provide feedback to truck drivers (Hickman and Hanowski, 2010). Similarly, the U.S. Aviation Safety Reporting System (ASRS) has been collecting confidential, voluntary reports of near misses from pilots, flight attendants, and air traffic controllers since 1976.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, return on investment analyses should be done as there has been only limited research published in this area (Boodlad & Chiang, 2014; Pitera, Boyle, & Goodchild, 2013), and IVMS is considered to be a fairly low-cost intervention in comparison to other safety technologies (Hickman & Hanowski, 2010). Given that motor vehicle crashes are consistently the leading cause of work-related death, in addition to affecting the general population, this research has addressed a significant public health problem.…”
Section: Practical Applicationsmentioning
confidence: 99%
“…Technologies such as collision warning systems and lane departure systems have been found to reduce risky driving behaviors (following too closely, lane departures), and rates of crashes (Chen, Jenkins, & Husting, 2004; Lee, McGehee, Brown, & Reyes, 2002; Merrikhpour, Donmez, & Battista, 2014). In addition to technologies that use sensors to detect nearby vehicles, there has been increased use of “on-board” or “in-vehicle” monitoring of driving behaviors (Hickman & Hanowski, 2010; Hickman, Hanowski, & Bocanegra, 2010; Horrey, Lesch, Dainoff, Robertson, & Noy, 2012; International Association of Oil and Gas Producers, 2014; Jones, 2016; Miller, Saldhana, Hunt, & Mello, 2013). These in-vehicle monitoring systems (IVMS) record vehicle maneuvers through sensors and can interface with the vehicle's computer; they may also utilize cameras to record video footage of the driver actively engaged in driving.…”
Section: Introductionmentioning
confidence: 99%
“…Un estudio del año 2010 publicado por el departamento de transportes de EEUU y elaborado por Virginia Tech Transportation Institute concluye que la combinación de dispositivos de monitoreo de seguridad y el entrenamiento conductual fue responsable de la reducción en la tasa de eventos relacionados con la seguridad en los grupos evaluados [24]. La investigación tuvo como objetivo evaluar la comercialización de dispositivos de bajo costo para administrar el comportamiento de los conductores.…”
Section: Análisisunclassified
“…Porcentaje de reducción de accidentes según AGEAS Estimación de la reducción de cantidad de accidentes 218,771 30% 65,631Si se extrapolan los datos del informe publicado por el Departamento de Transportes de EEUU[24], en el escenario pesimista, la reducción de accidentes sería de 38,1%, y en el escenario más optimista la reducción podría alcanzar el porcentaje del 52,2%. En la tabla V se muestran estos porcentajes aplicados a los datos históricos de la cantidad de reclamos para el INS en los años 2014 y 2015, que equivaldría a una reducción entre 83,132 y 113,760 casos.15 th LACCEI International Multi-Conference 2017: "Global Partnerships for Development and Engineering Education", 19-21 July 2017, Boca Raton, Florida, USA.…”
unclassified